INVESTIGATING THE RELATIONSHIP BETWEEN KEY ACCOUNT MANAGEMENT PERFORMANCE AND REPEAT ORDERS: DOES THE LENGTH OF THE RELATIONSHIP MATTER? - Nor Azila Mohd. Noor; Kawsar Ahmad (Asian Academy of Management Journal, 2014)
While a significant amount of research has examined the effectiveness of key account management, there is a surprising lack of studies that examine the dyadic outcome of key account management performance. The present research aims to examine the influence of key account management performance on the key account repeat orders outcome. The study empirically tests hypotheses with the data collected through a self-administered survey from 112 garment companies with a 100% export-oriented business. The results indicate that key account management performance significantly influences the buyer’s repeat order behaviour. We failed to prove the moderating effect of the length of the relationship on the relationship between key account management performance and repeat orders. We provide the theoretical, methodological and managerial implications as well as the limitations and directions for future research.